2000
DOI: 10.1007/s002490050002
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ray footprinting and fluorescence polarization anisotropy of a 30-mer synthetic DNA fragment with one 2′-deoxy-7-hydro-8- oxoguanosine lesion

Abstract: The influence of the oxidative lesion 2'-deoxy-7-hydro-8-oxoguanosine (8-oxodG) on some conformational properties of DNA has been studied. Four 30-mer duplexes of the form [5'-GATCCTCTAGAGTC[G(*) or G]ACCTGCAGGCATGCA-3']:[3'-CTAGGAGATCTCAG[C or A]TGGACGTCCGTACGT-5'], in which G(*) is the 8-oxodG lesion, were synthesized in order to compare the effect of the GA mismatch and of the damaged G(*)C and G(*)A forms with the normal GC. Spectroscopic measurements performed by means of UV denaturation and circular dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…Those were combined with ten additional values reported previously for 27 bp oligomers [2] to create a data set containing 53 torsion elastic constants. In earlier studies, the same group of Pedone, Barone, Mazzei and coworkers also reported torsion elastic constants for other 27 bp DNA, RNA, and DNA-RNA hybrid duplexes and also for a 30 bp DNA containing a lesion [3][4][5][6]. Prior investigations of duplexes containing V36 bp by other groups were unable to obtain reliable estimates of the torsion elastic constants, and no values were reported [7][8][9][10].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Those were combined with ten additional values reported previously for 27 bp oligomers [2] to create a data set containing 53 torsion elastic constants. In earlier studies, the same group of Pedone, Barone, Mazzei and coworkers also reported torsion elastic constants for other 27 bp DNA, RNA, and DNA-RNA hybrid duplexes and also for a 30 bp DNA containing a lesion [3][4][5][6]. Prior investigations of duplexes containing V36 bp by other groups were unable to obtain reliable estimates of the torsion elastic constants, and no values were reported [7][8][9][10].…”
Section: Introductionmentioning
confidence: 92%
“…The objectives of the present study are (1) to show that two 24 bp DNAs with a~5-fold ratio of torsion elastic constants and a 10% difference in r 0 can exhibit anisotropy decays that are practically indistinguishable for all times, tN1 ns; (2) to show that a and r 0 cannot be both be determined from FPA data for a 24 or 27 bp DNA using instruments like that of Pedone et al or that in our laboratory; (3) to note that for much longer DNAs, where a and r 0 can be simultaneously determined, the best-fit r 0 does not always exhibit the same value, 0.360, but instead varies over a range from 0.31 to 0.38, and is sensitive to Poisson noise and other variations in the experimental data; (4) to show that a rather small error in the assumed fixed value of r 0 can cause an extremely large error in the best-fit value of a; (5) to note that the values of R H and L reported by Pedone et al [2] for ten 27 bp duplexes differ from their expected values, and also among each other, by more than would be expected; and (6) to show that the 4.4-fold span of a-values reported by Pedone et al can be obtained by fitting FPA data that are simulated using a single value of a and modestly different r 0 values within the previously observed range of such values. The likelihood of validity of the 53 values reported by Pedone et al [1] is discussed in detail.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The reduced protein binding anity can be due to DNA structural or¯exibility changes. Until now no global structural changes but only some dierences in thermal and thermodynamic properties [8,9] and subtle changes to DNA dynamics were evidenced for short oligomers containing one oxoG [10].…”
Section: Introductionmentioning
confidence: 99%